The Marks of Scripture : rethinking the nature of the Bible - Castelo, Daniel, 1978-; Wall, Robert W. (Grand RApids, Michigan.: : Baker Academic, 2019)
"A theologian and a biblical scholar work out the four Nicene marks of the church (one, holy, catholic, apostolic) as marks of Scripture, offering a new way of thinking about the Bible"--
The ontology and teleology of Scripture -- Speaking of Scripture -- Unity -- Holiness -- Catholicity -- Apostolicity -- The church's practice of Scripture.
Includes bibliographical references and indexes.
Keywords: Bible -- Theology; Nicene Creed; Church -- Marks